Toxicity, risk factors and management of cisplatin-induced toxicity: A prospective study. (October 2020) - Ben Ayed, Wiem; Ben Said, Azza; Hamdi, Adel; Mokrani, Amina; Masmoudi, Yosri; Toukabri, Imen; Limayem, Imen; Yahyaoui, Yosra
Background and propose: Cisplatin is a cytotoxic drug that triggers several toxicities. However, nephrotoxicity and ototoxicity remain major clinical limitations. The aim of our study was to evaluate the incidence of chemotherapy toxicity induced by cisplatin and to analyze the influence of risk factors in the Tunisian population. Methods: We performed a prospective descriptive study in a period of four months. Patients were eligible if they had pathologically confirmed malignancies and treated with cisplatin-regimen chemotherapy. Nephrotoxicity and digestive toxicity were graded according to the World Health Organization toxicity scale and ototoxicity was scored clinically according to the Common Terminology Criteria for Adverse Events (CTCAE). Multivariate logistic regression analysis was performed to evaluate the influence of clinical variables on cisplatin-induced toxicity. Results: A total of 150 patients were included. Forty-four percent of patients developed cisplatin-regimen toxicity: 15% developed cisplatin-induced nephrotoxicity, 9% cisplatin-induced ototoxicity and 27% digestive toxicity. In the multivariate analysis, age >65 years (OR= 6.129, p = 0.010), metastatic cancer (OR = 0.171, p = 0.007) and cumulative dose (OR= 1.004 mg/m 2 ; p = 0.042) were strong predisposing factors for CDDP-induced nephrotoxicity. The cumulative dose was an independent prognostic indicator for digestive toxicity (OR = 0.997, p = 0.002). Conclusion: In our study, age >65 years and metastatic cancer were risk factors for cisplatin-induced nephrotoxicities. We also found the correlation between cumulative dose and nephrotoxicity or digestive toxicity.